Семантична структура номінативних речень англійської та української мов - Коцюба, З.Г. (Мовознавство, 2002)
Зауважено, що семантична спеціалізація номінативних речень полягає у ствердженні буття предметів або явищ. З урахуванням основного та супровідних значень виділено буттєві, оцінні номінативні речення (в обох мовах), вказівні (лише в українській мові). Проаналізовано якісну та кількісну конвергенції та дивергенції англійських та українських номінативних речень цих семантичних типів. The semantic essence of nominal sentences consists in the assertion of the existence of objects or phenomena. The concomitant meaning may be imparted on the basic one and as a result the following semantic types of nominal sentences are shaped: existential, evaluative (in both languages), demonstrative (in Ukrainian only). This article presents the analysis of qualitative and quantitative convergencies and divergencies of English and Ukrainian nominal sentences of the above-mentioned semantic types.